Righting past wrongs: A superintendent’s social justice leadership for dual language education along the U.S.-Mexico border - DeMatthews, David; Izquierdo, Elena; Knight, David S. (Education Policy Analysis Archives, 2017)
The role of superintendents in adopting and developing dual language education and other equity-oriented reforms that support the unique needs of Latina/o emergent bilinguals is a relatively unexplored area in educational leadership and policy research. Drawing upon theories of social justice leadership, this article examines how one superintendent in the El Paso Independent School District (EPISD) engaged in leadership to address injustices against Mexican and Mexican-American emergent bilinguals through the implementation of district-wide dual language education. EPISD provided a strategic site for this study because the previous superintendent and administration were part of a large-scale cheating scandal that “disappeared” hundreds of Mexican and Mexican-American students. This study highlights the important role of the superintendent in supporting equity-oriented school reforms such as dual language education, identifies specific actions and values pertinent to social justice leadership at the district level, and describes the ways leaders can take advantage of political opportunities, frame educational injustices in ways that mobilize key stakeholders, and utilize networks and grassroots movements for social justice means. The article concludes with implications for future research.